Educational Dualism in Malaysia: Implications for Theory and Practice by Rosnani Hashim, Kuala Lumpur: Oxford University Press, 1996, 204 pp. (American Journal of Islam and Society, 1998)
Since World War II, Malaysia has undergone numerous reviews and changesin its educational policy at the primary, secondary, and tertiary levels. Reportsby Barnes, Fenn-Wu, Razak, Rahman Talib, and the Malaysian cabinet as wellas the formulation of a national educational philosophy have inspiredMalaysians and non-Malaysians to conduct research and thus produce severaltheses. Some are concerned with educational reform and ethnic responses, otherswith national development; some are concerned with national identity andnational integration, others with a national educational policy and teacher education;and still others are concerned with the New Economic Policy (NEP) andequality of educational opportunity.The book under review is one of a series of studies in the form of a doctoraldissertation on education. It seeks to investigate the problems of educationaldualism in Malaysia, particularly as it affects the Muslim. Its aim is to arrive ata viable solution through a genuine synthesis of the two systems so that Muslimsovercome their educational dilemma without alienating the non-Muslims.In the first chapter, it is stated that this study hopes to contribute to the resolutionof long-standing educational and social problems in Malaysia. It alsohopes to demonstrate lhe compatibility of faith and reason.Chapters 2, 3, and 4 trace the history of lhe educational systems in Malaysia,i.e., the traditional or Islamic educational system and the colonial education inthe nineteenth century in the Straits Settlement followed by the establishment ofvernacular education in the Malay states following the Pangkor Treaty of 1874.The period from the early twentieth century up to the World War II has witnessedthe increase of English and Malay vernacular schools, both in StraitSeUlements and Federated States.The year 1956 marked a milestone in the evolution of a national system ofeducation. That year an education committee was set up. It was led by DatoAbdul Razak bin Hussein, who recommended the introduction of common contentsyllabus and the compulsory study of national and English languages in allprimary and secondary schools in order to orient pupils with a Malayan outlook,to inculcate national consciousness, and to foster mutual understanding amongcitizen of vari ous races and religions.Chapter 4 describes the creation of the Rahman Talib report and the impact ofthe NEP on the decline of enrollment in religious schools to lhe transformation ...